1992
DOI: 10.1002/ar.1092320410
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage development: II. Early ontogeny of macrophage populations in brain, liver, and lungs of rat embryos as revealed by a lectin marker

Abstract: Earliest origins of macrophage populations in the central nervous system, the liver, and the lungs were studied in rat embryos aged between 10.5-11 days and 14 days of gestation, based on light and electron microscopic identification of macrophages using peroxidase-coupled isolectin B4 of Griffonia simplicifolia (GSA I-B4), which recognizes alpha-D-galactose groups on the cell membrane. During embryonic life macrophages and their precursors are GSA I-B4-positive and generally bereft of peroxidase-positive gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 28 publications
9
88
0
1
Order By: Relevance
“…We reasoned that the embryonic hindbrain was ideally suited to study the role of the early, yolk sac-derived macrophages in angiogenesis, because avian studies had demonstrated that they colonise the brain by crossing the pial membranes and roof plate concomitantly with, but independently of, blood vessels. 30,31 Using the dual blood vessel/macrophage marker IB4 in combination with the macrophage-specific markers F4/80 and IBA1, 29,32,33 we confirmed that yolk sac-derived macrophages colonized the embryonic mouse brain independently of vessels, as reported for the chick (supplemental Figure 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). We found that embryonic brain macrophages were always IB4-positive and that they expressed F4/80 by 11.5 dpc (Figure 1A-E; supplemental Figure 1).…”
supporting
confidence: 55%
“…We reasoned that the embryonic hindbrain was ideally suited to study the role of the early, yolk sac-derived macrophages in angiogenesis, because avian studies had demonstrated that they colonise the brain by crossing the pial membranes and roof plate concomitantly with, but independently of, blood vessels. 30,31 Using the dual blood vessel/macrophage marker IB4 in combination with the macrophage-specific markers F4/80 and IBA1, 29,32,33 we confirmed that yolk sac-derived macrophages colonized the embryonic mouse brain independently of vessels, as reported for the chick (supplemental Figure 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). We found that embryonic brain macrophages were always IB4-positive and that they expressed F4/80 by 11.5 dpc (Figure 1A-E; supplemental Figure 1).…”
supporting
confidence: 55%
“…During embryonic development fetal macrophages͞microglia are detected in the CNS around E8 in mice and E12 in rat (33,34), a time-point well before the end of neurogenesis but before the onset of gliogenesis. The role of microglia cells during CNS development is generally believed to be to remove dead cells by phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Isolectin B4 binds specifically to microglial and endothelial cells on sections of developing and adult rat CNS (Streit and Kreutzberg, 1987;Ashwell, 1991;Sorokin et al, 1992;Chamak et al, 1995). Microglial cells were stained with this lectin in the forebrain of both normal and hypothyroid newborn rats (P0).…”
Section: Microglial Development In Hypothyroid Ratsmentioning
confidence: 99%
“…2 B, P4 ). However, microglial cells were already present in the developing rat brain at E12 (Ashwell, 1991;Sorokin et al, 1992), 4 d before the beginning of MTU treatment (E16). Early transplacental transfer of thyroid hormones from the mother (Obregon et al, 1984;Porterfield and Hendrich, 1992) therefore might have influenced the early fetal development of the microglial cells.…”
Section: Thyroid Hormone Favors Microglia Expansion: Early Postnatal mentioning
confidence: 99%